Antibodies to age-β2glycoprotein I in patients with anti-phospholipid antibody syndrome. (15th February 2016) - Sorice, M; Buttari, B; Capozzi, A; Profumo, E; Facchiano, F; Truglia, S; Recalchi, S; Alessandri, C; Conti, F; Misasi, R; Valesini, G; Riganò, R
Summary: Anti-phospholipid antibody syndrome (APS) is a systemic autoimmune disease characterized clinically by arterial and/or venous thromboses, recurrent abortions or fetal loss and serologically by the presence of 'anti-phospholipid antibodies' (aPL). The main target antigen of the antibodies is β2 glycoprotein I (β2 GPI). Post-translational oxidative modifications of the protein have been widely described. In this study we aimed to analyse sera reactivity to glucose-modified β2 GPI (G-β2 GPI). Sera collected from 43 patients with APS [15 primary APS (PAPS) and 28 APS associated with systemic lupus erythematosus (SLE) (SAPS)], 30 with SLE, 30 with rheumatoid arthritis (RA) and 40 healthy subjects were analysed by an enzyme-linked immunosorbent assay (ELISA) using a G-β2 GPI. Nine of 15 consecutive PAPS out-patients (60%) and 16 of 28 SAPS (57.1%) showed serum antibodies [immunoglobulin (Ig)G class] against G-β2 GPI (anti-G-β2 GPI) by ELISA. The occurrence of anti-G-β2 GPI was significantly higher in APS patients compared to patients suffering from SLE. No RA patients or control healthy subjects resulted positive for anti-G-β2 GPI. Of note, aG-β2 GPI prompted to identify some APS patients (four PAPS and seven SAPS), who were negative in the classical anti-β2 GPI test. Moreover, in APS patients, anti-G-β2 GPI titre was associated significantly with venous thrombosis and seizure in APS patients. This study demonstrates that G-β2 GPI is a target antigen of humoral immune response in patients with APS, suggesting that β2 GPI glycation products may contain additional epitopes for anti-β2 GPI reactivity. Searching for these antibodies may be useful for evaluating the risk of clinical manifestations.